2017
DOI: 10.1111/jfd.12735
|View full text |Cite
|
Sign up to set email alerts
|

Cardiomyopathy syndrome in Atlantic salmon Salmo salar L.: A review of the current state of knowledge

Abstract: and 2011 were significant discoveries that gave new impetus to the CMS research.In Norway, CMS usually causes mortality in large salmon in ongrowing and broodfish farms, resulting in reduced fish welfare, significant management-related challenges and substantial economic losses. The disease thus has a significant impact on the Atlantic salmon farming industry. There is a need to gain further basic knowledge about the virus, the disease and its epidemiology, but also applied knowledge from the industry to enabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
53
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 48 publications
1
53
0
1
Order By: Relevance
“…The genome size of PMCV is 6,688 bp and consists of three open reading frames (ORFs) (Haugland et al, ). Piscine myocarditis virus has been classified as a toti‐like virus due to similarities with viruses in the Totiviridae family and was the first toti‐like virus found to infect vertebrates (Garseth, Fritsvold, Svendsen, Bang Jensen, & Mikalsen, ). However, in 2016 two new toti‐like viruses were identified in golden shiner ( Notemigonus crysoleucas Mitchill) (Mor & Phelps, , ).…”
Section: Introductionmentioning
confidence: 99%
“…The genome size of PMCV is 6,688 bp and consists of three open reading frames (ORFs) (Haugland et al, ). Piscine myocarditis virus has been classified as a toti‐like virus due to similarities with viruses in the Totiviridae family and was the first toti‐like virus found to infect vertebrates (Garseth, Fritsvold, Svendsen, Bang Jensen, & Mikalsen, ). However, in 2016 two new toti‐like viruses were identified in golden shiner ( Notemigonus crysoleucas Mitchill) (Mor & Phelps, , ).…”
Section: Introductionmentioning
confidence: 99%
“…Findings indicate that the most important, known reservoir for the virus is farmed salmon. An overview of known and investigated sources is presented in the review recently published by Garseth and colleagues (Garseth, Fritsvold, Svendsen, Bang Jensen, & Mikalsen, 2018).…”
mentioning
confidence: 99%
“…The disease has been linked to piscine myocarditis virus (PMCV), a double stranded RNA virus that resembles members of the Totiviridae family (Løvoll et al, 2010;Haugland et al, 2011). First detected in farmed Atlantic salmon in Norway in 1985 (Amin and Trasti, 1988), outbreaks have since been reported in other geographical regions and countries including the Faroe Islands, Scotland, Ireland and possibly Canada (Rodger and Turnbull, 2000;Brocklebank and Raverty, 2002;Garseth et al, 2018). This disease is of major concern since it can pose significant financial burden to both farmers and to the industry, as it usually affects the brood fish or grow-out fish at their later life stages in sea (Svendsen and Fritsvold, 2009;Garseth et al, 2018), where considerable amount of recourses have already been allocated for the rearing and husbandry of the animals.…”
mentioning
confidence: 99%
“…apoptosis. Further, studies have reported large, inter-individual variation in Atlantic salmon's response to PMCV, regarding both the progression and the pathological outcomes of the disease Garseth et al, 2018). While some fish seemed to be able to clear or significantly reduce the level of the virus from 6-10 weeks post infection and exhibit little evidence of disease pathology, other fish retained high loads of virus and elevated heart tissue damage .…”
mentioning
confidence: 99%
See 1 more Smart Citation